The Effect of Workload and Self Efficacy on Employee Performance During the Covid-19 Pandemic - Arif Rahman Hakim; Aniek Rumijati; Rizki Febriani (Jurnal Bisnis dan Manajemen, 2022)
This study aims to determine the partial effect of workload, self-efficacy, job satisfaction on performance, to determine the partial effect of workload and self-efficacy on job satisfaction and to determine whether job satisfaction mediates the partial effect of workload and self-efficacy on performance. This research was conducted on employees in the education industry with a total of 81 respondents. The sampling technique uses simple random sampling. Data collection was carried out using interviews and questionnaires. The data analysis technique uses path analysis with the Smart PLS (Partial Least Square) program. The results showed that workload had a positive and significant effect on performance, workload had a positive and significant effect on job satisfaction, self-efficacy had a positive and not significant effect on performance, self-efficacy had a positive and significant effect on job satisfaction, job satisfaction had a positive and significant effect on performance, workload has a positive and insignificant effect on performance through job satisfaction and self-efficacy has a positive and significant effect on performance through job satisfaction.